2001
DOI: 10.1046/j.1365-2249.2001.01634.x
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γsynergizes with TNF-αbut not with viableH. pyloriin up-regulating CXC chemokine secretion in gastric epithelial cells

Abstract: SUMMARYHelicobacter pylori colonizes the gastric epithelial surface and induces epithelial cells to increase production of the neutrophil attractant IL-8. Little is known about the role of the gastric epithelium in regulating mucosal T cell trafficking. We therefore characterized constitutive and regulated epithelial expression of the CXC chemokines IP-10, I-TAC and Mig, which specifically attract CXCR3 expressing CD4 1 T cells. Human gastric epithelial cell lines (AGS, Kato III, NCI) were used to characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 37 publications
3
32
1
Order By: Relevance
“…Costimulation with H. pylori and IFN-g augmented IP-10 production in all cell lines, whereas stimulation with bacteria alone failed to do so ( Fig. 1B), which indicates that multiple stimuli are required for IP-10 expression in H. pylori-stimulated gastric epithelial cells, a finding consistent with that of a previous report (42). Indeed, NOD1 activation appears to be important in this regard, as IP-10 production was significantly reduced in NOD1 siRNA-treated AGS cells as compared with control cells (p , 0.0001; Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Costimulation with H. pylori and IFN-g augmented IP-10 production in all cell lines, whereas stimulation with bacteria alone failed to do so ( Fig. 1B), which indicates that multiple stimuli are required for IP-10 expression in H. pylori-stimulated gastric epithelial cells, a finding consistent with that of a previous report (42). Indeed, NOD1 activation appears to be important in this regard, as IP-10 production was significantly reduced in NOD1 siRNA-treated AGS cells as compared with control cells (p , 0.0001; Fig.…”
Section: Resultssupporting
confidence: 91%
“…1, 2), indicating that multiple stimuli are required for the expression of these chemokines in gastric epithelial cells. This finding is consistent with previous studies demonstrating synergism between IFN-g and NFkB signaling pathways (42,53), but differs from the findings of a recent study, which reported robust IP-10 induction in response to a synthetic NOD1 ligand, iE-DAP (54). Further investigation is necessary to determine the mechanism of H. pylori-induced IP-10 production by gastric epithelial cells.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have demonstrated that MIG expression is upregulated synergistically by stimulation with TNF-a and IFN-g indicating cytokine-regulated expression of inflammatory genes. 23,24 However, in the present study, the MIG promoter was activated by TNF-a but not by IFN-g. Although we do not know the reason why our result differed from those of the previous report cannot be explained, the mechanisms activating the MIG promoter may differ according to cellular lineage and differentiation stages.…”
Section: Discussioncontrasting
confidence: 75%
“…Moreover, IFN-g and TNF-a have been demonstrated to positively regulate the transcription of MIG gene. 23,24 As shown in Figure 3e, although IFN-g had no effect, TNF-a increased the MIG promoter activity in 293 cells when expression constructs of MUM1 and PU.1 were cotransfected.…”
Section: Mum1 Activates the Mig Promoter In Cooperation With Pu1mentioning
confidence: 85%
“…Interferon-inducible T cell ␣ chemoattractant (I-TAC, or CXCL11) is another potent ligand for CXCR3 that is induced in a wide range of human tissues by IFN␥ (50). I-TAC is expressed together with IP-10 and Mig in some epithelial cells, such as gastric epithelial cells (51) and bronchial epithelial cells (52). It is possible that I-TAC, along with IP-10 and Mig, is also involved in the SS salivary gland lesions.…”
Section: Discussionmentioning
confidence: 99%